Commentary on Galatians - Jerome, Saint, -419 or 420 (Fathers of the church, 2010)
"Prior to the middle of the fourth century, the exegesis of St. Paul had been monopolized by Greek and Syriac commentators. Then, in the space of half a century (c. 360 - c. 409), there appeared no less than 52 commentaries by six different Latin authors. This sudden flurry of literary activity has been dubbed the western "Renaissance of Paul." Jerome's commentaries on four Pauline epistles (Galatians, Ephesians, Titus, Philemon), which he composed in 386 shortly after establishing himself in Bethlehem, occupy a central place in this relatively short but prolific segment of the history of Pauline exegesis in Latin. Jerome was the greatest biblical scholar of the ancient Latin church, and his Commentary on Galatians is one of the crowning achievements of his illustrious career. It far outclasses the five other contemporary Latin commentaries on Galatians in its breadth of classical and patristic erudition, Hebrew and Greek textual criticism of the Bible, and expository thoroughness. It is unique also because it is the only one of the Latin commentaries to make the Greek exegetical tradition its main point of reference. Jerome's Commentary in fact preserves, in one form or another, a treasure-trove of otherwise lost Greek exegesis, particularly Origen's Commentary on Galatians, from which he worked very closely when composing his own work. Jerome's Commentary on Galatians is presented here in English translation in its entirety. The introduction and notes situate the Commentary in its historical, exegetical, and theological contexts and also provide extensive coverage of ancient and modern scholarly debates about the interpretation of Paul's epistle."--Publisher's website